Addressing Challenges and Opportunities of "Less Well-Understood" Adaptive Designs. (January 2017) - He, Weili; Gallo, Paul; Miller, Eva; Jemiai, Yannis; Maca, Jeff; Koury, Ken; Fan, Xiaoyin Frank; Jiang, Qi; Wang, Cunshan; Lin, Min
The draft adaptive design guidance released by FDA in 2010 included references to adaptive study designs that were described as "less well-understood." At that time, there was relatively little regulatory experience with such designs, and their properties were felt to be insufficiently understood. In order to promote greater use of adaptive designs, especially those categorized as less well-understood, the Best Practice Subteam of the DIA Adaptive Designs Scientific Working Group (ADSWG) has worked on describing and characterizing these designs, identifying challenges associated with them and suggesting improvements to design or study conduct aspects that might make them more acceptable. This paper summarizes the work from the subteam.